Spirit Inovasi Pendidikan Islam dalam Slogan “Tempemu Tak Sehangat Tempeku” Studi Warung Mendoan Amba Suci Sotang - Sakir, Moh; Syam, Robingun Suyud El (STAI Denpasar Bali, 2023)
Serious technological changes are taking place in the world and especially in the field of information and communication technology. These changes have had a significant impact on all aspects of people's lives and activities, including aspects of slogans. This article presents a detailed analysis of the spirit of innovation in Islamic education in the slogan